Szanse i ryzyka kształcenia online dla akademickiej relacji mistrz – uczeń - Pietrzykowski, Adam (Kultura-Społeczeństwo-Edukacja, 2022)
The article describes the opportunities and risks of Master – Student relation in the academic, online learning setting. The article begins with the analysis of Master – Student relation by presenting issues regarding the traditionally interpreted person of the master as well as by presenting the obstacles and expectations faced by students. Further on, advantages and disadvantages of computermediated communication (CMC) of the relation are discussed. Based on the research in CMC which, includes the hyper-personal model and the Media Naturalness Theory, the ambivalence of building an authentic, based on the ethical foundations, and a long-lasting interpersonal relationship, is shown. Finally, key risk areas are discussed, in particular reductionist online learning models implemented by the neoliberal agenda in university education, and doubts about the effectiveness of value-oriented education in a virtual environment.